Aumento do volume labial com o uso de toxina botulínica - Pinto, Camila Araujo Scharf; Rebellato, Priscila Regina Orso; Schmitt, Juliano Vilaverde [UNESP]; de Torre, Deborah Skusa (GN1 Sistemas e Publicacoes, 2017)
Introduction: The application of botulinum toxin in the perioral region is a minimally invasive procedure that leads to substantial improvement in the signs of aging in addition to increasing the volume of the lips. However literature on this procedure is still scarce. Objective: To evaluate changes in shape and volume of the lips, as well as the patients' satisfaction after the application of botulinum toxin in perioral lines. Methods: Nineteen patients underwent evaluation, photographic record and measurements following the application of botulinum toxin in the perioral region, being subsequently assessed for changes in the lips and satisfaction. Results: Most of the patients rated their lips as moderately or significantly more attractive after the application of botulinum toxin (p = 0.039). Fifteen women deemed the changes in the lips as a major factor in the overall improvement of their faces. Conclusions: The use of botulinum toxin in the perioral region leads to the elevation of the upper lip, causing the shortening of the philtrum and the extension of the vermilion. The application of botulinum toxin in the vermilion's border leads to the relaxation of the orbicularis muscle, favoring a more intense tonus effect arising from the upper lip lifting muscles. The patients' satisfaction with the appearance of their lips was evaluated by four additional questions (linked to the lip's shape, volume, attraction and beauty), receiving positive answers. Side effects were minimal.
Lip volumization using botulinum toxin
Keywords: Botulinum toxins; Lip; Type a